Efficacy of Reciproc Blue and ProDesign R reciprocating files in the removal of filling material: An integrative literature review (Research, Society and Development, 2021)
The aim of the present study was to conduct an integrative review on the mechanical properties of Reciproc Blue and ProDesign R reciprocating systems and the efficacy of these files in removing root filling materials. The search was carried out on the PUBMED using following combinations of scientific terms: Reciproc Blue, ProDesign R, resistance, mechanical properties, thermal treatment and endodontic retreatment. The research identified 64 articles, of which 29 were selected for the present study. The articles demonstrated the importance of thermomechanical treatment on elasticity and stiffness of Reciproc Blue and ProDesign R endodontic instruments compared to other systems. It was also observed that both files are effective in removing the filling material from the root canal, however both systems failed to remove it completely.